Pacemaker and defibrillator therapy in pediatrics and congenital heart disease. (September 2008) - Chun, Terrence
Pacemakers and defibrillators have a growing use in pediatrics and in patients with congenital heart disease, but they present unique problems and implications for their implantation and follow-up. Congenital and surgically acquired rhythm disturbances are common, but the efficacy of device therapy is not well established in these patient groups. The diversity and complexity of pediatric patients and congenital heart disease make device management a highly individualized art. There are technical issues related to device implantation that have necessitated novel approaches to using leads and device that were not designed with children specifically in mind. The current guidelines and indications for implantable device therapy for children and congenital heart disease are reviewed, as well as some of the specific limitations and problems encountered.